2002
DOI: 10.1080/09593332308618367
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Cr(VI) and Bioaccumulation of Chromium by Gram Positive and Gram Negative Microorganisms not Previously Exposed to CR-Stress

Abstract: Resistance to Cr(VI) is usually associated with its cellular exclusion, precluding enrichment techniques for the isolation of organisms accumulating Cr(VI) via bioreduction to insoluble Cr(III). A technique was developed to screen for potential Cr(VI) reduction in approx. 2000 isolates from a coastal environment, based on the non-specific reduction of selenite and tellurite to Se0 and Te0, and reduction of tetrazolium blue to insoluble blue formazan. The most promising strains were further screened in liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 0 publications
2
36
0
Order By: Relevance
“…To further highlight such adaptation, recent investigations of terrestrial and marine bacterial isolates belonging to the genera Aeromonas, Bacillus, Myxococcus, Pantoea, Pseudomonas, Rahnella, and Vibrio demonstrated that Cr, Pb, and U were removed from solution as phosphate minerals under both oxic and anoxic growth conditions [57,60,74,152,[154][155][156][157][158]. Our recent work further examined lead and 6 Advances in Ecology uranium precipitates produced by Rahnella sp.…”
Section: Phosphatase-mediated Biomineralizationmentioning
confidence: 99%
See 2 more Smart Citations
“…To further highlight such adaptation, recent investigations of terrestrial and marine bacterial isolates belonging to the genera Aeromonas, Bacillus, Myxococcus, Pantoea, Pseudomonas, Rahnella, and Vibrio demonstrated that Cr, Pb, and U were removed from solution as phosphate minerals under both oxic and anoxic growth conditions [57,60,74,152,[154][155][156][157][158]. Our recent work further examined lead and 6 Advances in Ecology uranium precipitates produced by Rahnella sp.…”
Section: Phosphatase-mediated Biomineralizationmentioning
confidence: 99%
“…Furthermore, contaminated sites that are characterized by acidic to circumneutral porewater pH represent environments that can support stable mineral formation (Figures 2(a) and 2(b)), provided that carbonates are not present in significant concentrations (i.e.,P CO 2 < 10 −3.5 atm) [176,177]. Interestingly, investigations of microbial reduction of Cr, Np, Pu, and U have been shown to support subsequent phosphate precipitation reactions via thermodynamic modeling, chromatographic separation of actinides based on valence state, and X-ray analytical methods [154,155,172,178,179]. Unlike U, that is capable of forming phosphate minerals in both hexavalent and tetravalent states [50,179], the reduction of Cr, Np, and Pu is initially required for these contaminants to participate in phosphate precipitation reactions [154,155,172,178].…”
Section: Challenges For In Situ Immobilization Of Metals and Radionucmentioning
confidence: 99%
See 1 more Smart Citation
“…The best-documented organism for metal phosphate biomineralization, a Citrobacter sp., (now reclassified as a Serratia sp. on the basis of molecular methods, the presence of the phoN phosphatase gene and the production of pink pigment under some conditions (Pattanapipitpaisal et al 2002) grows well on cheaply available substrates and viable cells are not required for metal uptake since this relies on hydrolytic cleavage of a supplied organic phosphate donor (Macaskie et al 1992). The expense of adding organic phosphate was calculated to be the single factor which limited the economic viability of this approach (Roig et al 1995); moreover organophosphorus compounds are often highly toxic.…”
Section: Biomineralization Via Microbially Generated Ligandsmentioning
confidence: 99%
“…Many aerobic and anaerobic bacteria have been isolated from different habitats exhibited their potential capacity to secrete cellulases (Nakamura and Kitamura, 1982;Schwarz, 2001;Milala et al, 2005;Immanuel et al, 2006). Many strains belong to genus Exiguobacterium have wide applications in biotechnological, industrial and agricultural fields (Bogdanova et al, 2001;Pattanapipitpaisal et al, 2002;Anderson and Cook, 2004;Romsaiyud et al, 2005;Kumar et al, 2006;Okeke, 2008). Moreover, various enzymes such as protease, esterase, guanosine kinase, dehydrogenase and ATPases were purified and characterized from several Exiguobacterium strains (Usuda et al, 1998;Suga and Koyama, 2000;W ada et al, 2004;Hwang et al, 2005;Kasana and Yadav, 2007;Hara et al, 2007).…”
Section: Introductionmentioning
confidence: 99%